Penolakan Vaksinasi Covid-19 Di Indonesia: Relasinya Terhadap Perilaku Keagamaan Dan Kepercayaan Masyarakat Pada Negara - Muhdar, HM; Kadim, Immawan Muhajir; rahma, St; Mohune, Pikran; Asipu, Zulkifli Repikasa (Institut Agama Islam Sumatera Barat Pariaman, 2024)
The COVID-19 pandemic and its vaccination are still central issues in the global world today, although in its development it is slowly starting to be resolved, including in Indonesia. However, several researchers found that there are still groups of people in parts of the world, including Indonesia, who do not want or refuse to get the COVID 19 vaccination on the grounds that vaccine safety, vaccine side effects, religion, financing, and feel confident that they do not need a vaccine. This means that Covid-19 vaccination still causes problems in people's lives. On this basis, researchers are interested and highlight two things, namely whether there is a correlation between refusing Covid-19 vaccination and religious behavior and people's trust in their country with the aim of analyzing and explaining the correlation between refusing Covid-19 vaccination and religious behavior and people's trust in the country. The method used is the mix method. First, a quantitative method with the main instrument being a questionnaire given to 150 respondents. Second, the qualitative method with the main instrument of interviews functions to provide a more complete explanation of the findings in the quantitative method. The research results found that resistance to Covid-19 vaccination in Indonesia is still quite large and in relation to the religious behavior of people who are categorized as religious are in the weak and significant category. So religious behavior does not provide great potential in preventing Covid-19 vaccination. Public trust in the state is in the doubtful category, in relation to refusal of Covid-19 vaccination it is in the moderate and significant category. The greater the public's trust, the greater the potential for awareness to carry out Covid-19 vaccination. For this reason, it is hoped that the government will eliminate public doubts and build public trust in managing the Covid-19 vaccination.